Investigating the Relationship Among English Language Learning Strategies, Language Achievement, and Attitude - Habók, Anita; Magyar, Andrea; Molnár, Gyöngyvér (Frontiers in Psychology, 2022)
The main objective of the study was to ascertain whether English as a foreign language learners with various levels of English language achievement differ significantly in applying foreign language learning strategies. We also aimed to explore strategy use frequency in connection with attitude towards English language learning. Data were collected from 1653 lower secondary students in Hungary through a revised version of the previously developed online Self-Regulated Foreign Language Learning Strategy Questionnaire (SRFLLSQ; Habók & Magyar, 2018) based on Oxford’s Strategic Self-Regulation (S2R) Model (2016). The findings point to statistically significant differences in the frequency of English language strategy use among more and less proficient learners. Quantitative analyses also reported that, in spite of the students stated low or moderate levels of strategy use, it turned out as a statistically significant predictor of foreign language attitude and language achievement. The results draw attention to the relevance of strategy research in foreign language teaching as well as encourages strategy teaching within language instruction.